Experimental Study on the Influence of Crack Penetration Rate on Strength Properties of Expansive Soil - HU Bo, WANG Shuai, SUN Hui, GENG Hong-bin, WANG Qing, ZHOU Hong-jun (长江科学院院报)
[Objective] This study aims to break through traditional limitations by quantifying the influence mechanism of crack penetration rate on the strength characteristics of expansive soil through laboratory experiments. It seeks to establish a predictive model for shear strength based on penetration rate, providing a scientific basis for evaluating the stability of engineering slopes. [Methods] A novel method was employed to simulate cracks using geomembranes. Triaxial specimens with varying crack penetration rates (0%, 33.3%, 50.0%, 66.7%) were prepared and subjected to consolidated drained triaxial tests. During the tests, interface strength parameters between the geomembrane and the soil were obtained through direct shear interface friction tests. Combined with the Mohr-Coulomb strength criterion and strength calculation methods for cracked surfaces, a composite strength analysis framework for the “soil block-crack” structure was established. Compared to traditional crack simulation methods, this technique enables precise control of crack geometry, effectively reproducing the crack development process and providing robust data support. [Results] Crack penetration significantly affected the mechanical behavior of expansive soils. As penetration rate increased, the stress-strain curves of the specimens exhibited a transition from strain hardening to strain softening. When the penetration rate increased from 0% to 66.7%, a distinct peak appeared under high confining pressure (400 kPa), and the peak strength decreased by 60.73%, indicating a pronounced increase in brittle failure characteristics. Under low confining pressure, the specimens exhibited no obvious peak strength and were mainly subject to plastic failure, with the stress-strain curve displaying mild strain softening. The ultimate deviatoric stress at failure was influenced by both confining pressure and crack penetration. With increasing penetration rate, the soil’s resistance to shear failure diminished, and the ultimate deviatoric stress decreased accordingly. This decline became more pronounced as confining pressure increased. When cracks were introduced into the specimen, they altered the stress concentration zones, promoting shear failure along the cracks. Obvious shear cracks appeared along the shear plane, and the failure mode shifted from bulging failure to dislocation failure along the crack surface. Shear strength was a key mechanical property representing soil failure characteristics. In this study, the strength parameters of specimens with cracks were calculated using the cracked-surface strength method, yielding accurate shear strength indices. When the crack penetration rate was 0%, the shear strength indices represented intact soil, with cohesion and internal friction angle of 37.6 kPa and 22.0°, respectively. When the penetration rate increased to 33.3%, cohesion and internal friction angle decreased to 30.7 kPa and 20.1°, down by 18.4% and 8.6% compared to the 0% case. At 50.0% penetration rate, these values further dropped to 27.6 kPa and 16.4°, decreasing by 26.6% and 25.5%, respectively. As penetration rate increased, the actual contact area between soil particles and crack surfaces grew, reducing frictional resistance along the shear plane. When the penetration rate reached 66.7%, cohesion and internal friction angle declined to 21.8 kPa and 15.2°, down by 42.0% and 30.9% from the 0% condition, indicating that cracks exerted a greater control over shear strength. Therefore, with increasing penetration rate, the shear strength parameters of the soil-crack surface consistently decreased. To further illustrate that the variation in shear strength parameters under different penetration rates was the result of the combined effect of soil blocks and cracks, this study established a comprehensive calculation formula for shear strength along the failure surface. A comparative analysis of the calculated and predicted shear strength values under different penetration rates showed that the deviation of the internal friction angle prediction from the experimental value ranged from -2.5% to 6.7%, and that of cohesion ranged from -19.7% to -3.3%, all within the allowable experimental error. [Conclusion] This study uses a novel simulation material to quantitatively analyze the influence of cracks on the strength properties of expansive soil, investigating the effect of cracks on shear failure patterns and strength characteristics. A comprehensive strength calculation formula is proposed to validate the influence of the integrated behavior of soil along the shear surface. The findings enrich the theoretical system of expansive soil crack mechanics and provide a reference for slope stability analysis in similar hydraulic engineering projects.